GIFT-AI: teaching the game and leveling the field: Peer and AI Review + Reflection in a business writing course - MacArthur, Marit; Minnillo, Sophia; Sperber, Lisa; Whithaus, Carl; Stillman, Nicholas (Frontiers in Communication, 2025)
Responding to educators’ concerns about how to address GenAI in professional writing assignments and courses, we present a tested pedagogical model that integrates GenAI feedback into writing curricula, with a particular focus on a Business Writing course with 34 students in 2024. The Peer and AI Review + Reflection (PAIRR) model follows this method: teachers scaffold major writing assignments so that students participate in peer review of a full draft, then elicit criteria-based feedback on the same draft from a chatbot. Next, students reflect on and critically assess both peer and chatbot-generated feedback and formulate revision plans. After revising, students compose a second reflection about how each kind of feedback influenced their revisions. In this paper, we motivate the PAIRR model, offer instructions for implementation, and share findings. We note the effectiveness of PAIRR in guiding students to critically interrogate AI output, build AI literacy, and prioritize their voices and writing goals while revising in response to peer and AI feedback. Addressing the particular challenges faced by multilingual international students in professional writing courses, we also showcase the affordances and utility of this model for these students. Finally, we discuss the applicability of PAIRR for a variety of writing courses.